Mental healthcare access among resettled Syrian refugees in Leipzig, Germany - Samantha F. Schoenberger; Kim Schönenberg; Daniela C. Fuhr; Yuriy Nesterko; Heide Glaesmer; Egbert Sondorp; Aniek Woodward; Marit Sijbrandij; Pim Cuijpers; Alessandro Massazza; Martin McKee; Bayard Roberts (Cambridge Prisms: Global Mental Health, 2024)
Our aim was to examine mental health needs and access to mental healthcare services among Syrian refugees in the city of Leipzig, Germany. We conducted a cross-sectional survey with Syrian refugee adults in Leipzig, Germany in 2021/2022. Outcomes included PTSD (PCL-5), depression (PHQ-9), anxiety (GAD-7) and somatic symptom (SSS-8). Descriptive, regression and effect modification analyses assessed associations between selected predictor variables and mental health service access. The sampling strategy means findings are applicable only to Syrian refugees in Leipzig. Of the 513 respondents, 18.3% had moderate/severe anxiety symptoms, 28.7% had moderate/severe depression symptoms, and 25.3% had PTSD symptoms. A total of 52.8% reported past year mental health problems, and 48.9% of those participants sought care for these problems. The most common reasons for not accessing mental healthcare services were wanting to handle the problem themselves and uncertainty about where to access services. Adjusted Poisson regression models (n = 259) found significant associations between current mental health symptoms and mental healthcare service access (RR: 1.47, 95% CI: 1.02–2.15, p = 0.041) but significance levels were not reached between somatization and trust in physicians with mental healthcare service access. Syrian refugees in Leipzig likely experience high unmet mental health needs. Community-based interventions for refugee mental health and de-stigmatization activities are needed to address these unmet needs in Leipzig.